Pengaruh Kepemimpinan, Motivasi, dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Pada Karyawan Perum Perumnas Kantor Regional V Semarang) - Kahar, Bahaudin; Rodhiyah, Rodhiyah; Prihatini, Apriatni Endang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
Every company needed human resources management to achieve success. Human resource management played an active role in improving performance of the employeethrough a number of variables that affect it, such as leadership, motivation, and workingdiscipline. Perum Perumnas Regional V Semarang was a public company engaged in the saleand development of national housing, but in fact there were still problem that cause adecrease in performance of the employee. So, the purpose in this study to identify and explainthe effect of leadership, motivation, and working discipline at Perum Perumnas RegionalOffice V Semarang.This type of research was explanatory. Data collection technique with interviews andquestionnaires against 62 respondents with saturated sampling technique. The analysistechnique used is quantitative and descriptive analysis using validity, reliability test, crosstabulation, correlation coefficient, coefficient of determination, simple and multipleregression analysis, as well as the significance test (t test and F test) with SPSS version 16.0for windows.The results and discussion, based on the categorization of leadership in company wasquite good, the work of each employee motivation was high, discipline of employee was highcategorization, and the performance of the employee at the company was quite well.Partially, leadership had positive and significant effect on performance of the employee, therelationship between the two variables was average with a correlation of (0.542), thecoefficient of determination of (28.2%), motivation had positive and significant effect on theperformance of regression coefficient, the relation between the two variables was high with acorrelation of ( 0.762), the coefficient of determination of (57.3%), working discipline hadpositive and significant effect on the performance of the regression coefficient, the relationbetween the two variables was high with a correlation of (0.760), the coefficient ofdetermination of (57%). Simultaneously leadership, motivation and working discipline hadpositive and significant effect on the performance of the regression coefficient Y = 1,877+0,124X1 + 0,410X2 + 0,372X3, the relationship of independent variables (X) and dependent(Y) was very strong with a correlation of (0.863), the coefficient of determination of (68.3%).The conclusion there was positive and significant influence between leadership,motivation, and working discipline on performance of the employee. The suggestion was thecompany need to pay attention to communication between leaders and employees in how toapproach, provide guidance and error correcting any work performed by employees, as wellas effort to improve employee work motivation by giving rewards and give a sanction againstemployees who violate the discipline of time (delay) firmly.